Pengaruh Media Pembelajaran Dan Keaktifan MahasiswaDalam Belajar Terhadap Hasil Belajar Mata KuliahAkuntansi Perusahaan Jasa Pada Mahasiswa ProgramStudi Pendidikan Akuntansi FKIP UMS Angkatan 2015 - Saputro, Bagus Adi, Drs.Sudarto HS. MM (2016)
The purpose of this study to determine: Effect of (1) a medium of learning for learning outcomes in an accounting class at the student services company Accounting Education Studies Program FKIP force UMS 2015 (2) the activity of the students in learning the learning outcomes of the course accounting services company in students of accounting Education FKIP force UMS 2015 (3) media learning and learning activity of students in the learning outcomes of the course the student services at the accounting firm accounting Education Studies Program FKIP UMS force in 2015. This study uses quantitative methods associative. The population in this experiment were students of Education Studies Program Accounting who take courses Accounting Services Company forces in 2015 is 251 students. The sampling technique using Proportional Random Sampling as many as 146 respondents. The necessary data and documentation obtained through a questionnaire that has previously been tested by validity and reliability testing. Data analysis technique used is multiple linear regression, t-test, F, R2 test, and the relative contribution and effective. Results of regression analysis regression equation: Y = 10.765 + 0,168X1 + 0,265X2. The conclusion of this study are: (1) learning media has a significant influence on the results of study subjects accounting services company. Based on t test (α = 5%) obtained t> t table is 3.723> 1.977. (2) the activity of students in the study have a significant effect on learning outcomes in an accounting class service company. Based on t test (α = 5%) obtained t> t table is 5.067> 1.977. (3) learning media and activeness of students in learning together have a significant effect on learning outcomes in an accounting class service company. Based on test results obtained Fhitung F> Ftable is 44.196> 3.059 at significance level of 5%. (4) Variable X1 gives the relative contribution of 40% and the effective contribution of 15.4%, X2 gives the relative contribution of 60% and the effective contribution of 22.8%. (5) The calculation result R2 obtained 0.382 means that 38.2% influence learning outcomes accounting subjects influenced by media services company learning and activeness of students in learning, while the remaining 61.8% is influenced by variables outside the research.